Bacteriophage therapy to reduce Campylobacter jejuni colonization of broiler chickens - Loc Carrillo, C.; Atterbury, Robert J.; El-Shibiny, A.; Connerton, Phillippa L.; Dillon, E.; Scott, A.; Connerton, Ian F. (American Society for Microbiology., 2005)
Colonization of broiler chickens by the enteric pathogen Campylobacter jejuni is widespread and difficult to prevent. Bacteriophage therapy is one possible means by which this colonization could be controlled, thus limiting the entry of campylobacters into the human food chain. Prior to evaluating the efficacy of phage therapy, experimental models of Campylobacter colonization of broiler chickens were established by using low-passage C. jejuni isolates HPC5 and GIIC8 from United Kingdom broiler flocks. The screening of 53 lytic bacteriophage isolates against a panel of 50 Campylobacter isolates from broiler chickens and 80 strains isolated after human infection identified two phage candidates with broad host lysis. These phages, CP8 and CP34, were orally administered in antacid suspension, at different dosages, to 25-day-old broiler chickens experimentally colonized with the C. jejuni broiler isolates. Phage treatment of C. jejuni-colonized birds resulted in Campylobacter counts falling between 0.5 and 5 log10 CFU/g of cecal contents compared to untreated controls over a 5-day period postadministration. These reductions were dependent on the phage-Campylobacter combination, the dose of phage applied, and the time elapsed after administration. Campylobacters resistant to bacteriophage infection were recovered from phage-treated chickens at a frequency of <4%. These resistant types were compromised in their ability to colonize experimental chickens and rapidly reverted to a phage-sensitive phenotype in vivo. The selection of appropriate phage and their dose optimization are key elements for the success of phage therapy to reduce campylobacters in broiler chickens.